Application of FRA Polar Plot Technique to Diagnose Internal Faults in Power Transformers - Abu-Siada, Ahmed; Aljohani, O. (IEEE, 2014)
Frequency response analysis (FRA) technique has become a popular and reliable diagnostic tool in detecting various winding deformation in power transformers. Although the popularity of FRA is growing rapidly, interpretation of FRA signature requires high expertise. While all frequency response analyzers currently used for FRA signature measurement are capable in plotting both magnitude and angle of either the transfer function or impedance of each transformer winding, only magnitude is used for fault identification and quantification. This paper presents a new technique for FRA signature interpretation. The proposed technique relies on incorporating both magnitude and angle of the FRA signature in one polar plot. Results show that, polar plot is more capable in identifying and quantifying faults within power transformer than using only the magnitude of FRA signature. The proposed technique is easy to implement in any frequency response analyzer.